Socioeconomic factors and childhood overweight in Europe: results from the multi‐centre IDEFICS study. Issue 1 (8th August 2012) - Bammann, K.; Gwozdz, W.; Lanfer, A.; Barba, G.; De Henauw, S.; Eiben, G.; Fernandez‐Alvira, J.M.; Kovács, E.; Lissner, L.; Moreno, L.A.; Tornaritis, M.; Veidebaum, T.; et al.
Summary What is already known about this subject Overweight and obesity can be linked to different parental socioeconomic factors already in very young children. In Western developed countries, the association of childhood overweight and obesity and parental socioeconomic status shows a negative gradient. Ambiguous results have been obtained regarding the association between socioeconomic factors and childhood overweight and obesity in different countries and over time. What this study adds European regions show heterogeneous associations between socioeconomic factors and overweight and obesity in a multi‐centre study with highly standardized study protoco. The strength of association between SES and overweight and obesity varies across European regions. In our study, the SES gradient is correlated with the regional mean income and the country‐specific Human development index indicating a strong influence not only of the family but also of region and country on the overweight and obesity prevalence. Objective To assess the association between different macro‐ and micro‐level socioeconomic factors and childhood overweight. Methods Data from the IDEFICS baseline survey is used to investigate the cross‐sectional association between socioeconomic factors, like socioeconomic status (SES), and the prevalence of childhood overweight. Differences and similarities regarding this relationship in eight European regions (located in Belgium, Cyprus, Estonia, Germany, Hungary, Italy, Spain and Sweden) are explored. 11 994 children (50.9% boys, 49.1% girls) and their parents were included in the analyses. Results In five of the eight investigated regions (in Belgium, Estonia, Germany, Spain and Sweden), the prevalence of childhood overweight followed an inverse SES gradient. In the other three regions (in Cyprus, Hungary and Italy), no association between SES and childhood overweight was found. The SES‐overweight association in a region was best explained by the country‐specific human development index and the centre‐specific mean income. For the investigated association between other socioeconomic factors and overweight, no clear pattern could be found in the different regions. Conclusion The association between socioeconomic factors and childhood overweight was shown to be heterogeneous across different European regions. Further research on nationwide European data is needed to confirm the results and to identify target groups for prevention.